2020
DOI: 10.1002/app.50100
|View full text |Cite
|
Sign up to set email alerts
|

Using design of experiments to understand and predict polymer microcapsule core‐shell architecture

Abstract: Microbubbles (MBs) have tremendous application in a number of fields and strategies to impart them with tunable properties are of great interest to the scientific community. We recently reported a robust platform to produce polymeric MBs (more appropriately termed polymeric microcapsules, PMCs) with highly tunable materials properties by controlling the self-emulsification of oilin-water emulsions. In this study, we used design of experiments to develop a model to predict PMC internal architectures and mean pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…Despite Zhang et al proposing the one-step microfluidic synthesis of polyelectrolyte microcapsules by combining an aqueous two-phase system and interfacial complexation in water/water/water double emulsion droplets, the oil-free microfluidic approaches are plagued by limited material options and low production rates. [7,8] Moreover, the manufacture of microfluidic devices contains additional manufacturing costs and complex surface treatment. [9] Thus, developing a simple and versatile method that enables the one-step generation of biocompatible microcapsules in large quantities under non-organic solvent conditions is still challenged.…”
Section: Introductionmentioning
confidence: 99%
“…Despite Zhang et al proposing the one-step microfluidic synthesis of polyelectrolyte microcapsules by combining an aqueous two-phase system and interfacial complexation in water/water/water double emulsion droplets, the oil-free microfluidic approaches are plagued by limited material options and low production rates. [7,8] Moreover, the manufacture of microfluidic devices contains additional manufacturing costs and complex surface treatment. [9] Thus, developing a simple and versatile method that enables the one-step generation of biocompatible microcapsules in large quantities under non-organic solvent conditions is still challenged.…”
Section: Introductionmentioning
confidence: 99%
“…DoE is used to systematically address cause and effect relations between the parameters in study and experimental outputs, enabling to build a model to mathematically predict an output [ 17 , 21 , 22 , 23 , 24 ]. The use of DoE was previously reported for the optimization of MCs obtained using several techniques, such as spray-drying, phase separation, solvent evaporation and in situ and interfacial polymerization [ 25 , 26 , 27 , 28 , 29 , 30 ]. Lock et al reported on the development of a model to predict the internal architecture and mean particle diameters of gas-filled polymeric MCs, produced using phase separation [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…The use of DoE was previously reported for the optimization of MCs obtained using several techniques, such as spray-drying, phase separation, solvent evaporation and in situ and interfacial polymerization [ 25 , 26 , 27 , 28 , 29 , 30 ]. Lock et al reported on the development of a model to predict the internal architecture and mean particle diameters of gas-filled polymeric MCs, produced using phase separation [ 26 ]. The authors considered concentration of emulsifier, stirring speed, and emulsion dilution as factors.…”
Section: Introductionmentioning
confidence: 99%